An experimental study of wave-in-deck loading and its dependence on the properties of the incident waves. (January 2020) - Ma, Li; Swan, Chris
Abstract: Recent advances in the description of extreme ocean waves have led to the definition of more severe design conditions. These changes include increases in the sea-state severity for a given return period, the nonlinear amplification of crest elevations beyond second-order and, perhaps most importantly, the occurrence of wave breaking in both intermediate and deeper waters. These developments raise important questions as to whether present design practice, commonly based upon simplified regular wave theories, provides a realistic estimate of the maximum design loads on fixed offshore structures. This is especially relevant if the applied wave load involves the loss of an effective air-gap and, the occurrence of wave-in-deck (wid ) loading; the latter believed to be the most common cause of failure in severe seas. To address these issues, an extensive laboratory study of wid loading has been undertaken. This paper presents the first part of the findings from this study; the aim being to provide an improved physical understanding of wid loading in a wide range of incident wave conditions. The study shows that the applied loads are critically dependent upon both the wave shape and the water particle kinematics arising at the highest elevations within the wave crest; both properties being strongly influenced by the occurrence of wave breaking, particularly wave over-turning. Indeed, the occurrence of wave breaking leads to markedly different load time-histories with important consequences for both the maximum applied load and the onset of a dynamic excitation. The results presented herein provide important guidance as to the effective modelling of these critical loading events.